Pengembangan Metode Pembelajaran Pendidikan Agama Islam yang Efektif melalui Pemanfaatan Teknologi Informasi dan Komunikasi - Wiwin Rif'atul Fauziyati; Mariana Mariana (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
This scientific work aims to examine and develop effective learning methods in the context of Islamic religious education by utilizing information and communication technology (ICT). Islamic religious education is an important aspect in character formation and understanding religious values in a society that is increasingly connected digitally. This research focuses on integrating ICT in the Islamic religious learning process and investigates how the use of ICT can increase learning effectiveness. The research method used is literature analysis to identify the latest approaches in Islamic religious education that utilize ICT. Furthermore, this research involves designing and developing a learning model that combines the principles of Islamic religious education with available information technology. The research results show that the use of ICT in Islamic religious learning can increase student involvement, expand access to religious learning resources, and enable more interactive and personalized learning. The development of this learning method can make a positive contribution in advancing Islamic religious education in this digital era, enabling the younger generation to have a deeper understanding of religion and its moral values.